SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KARYAWAN TERBAIK MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING STUDI KASUS RUMAH SAKIT HATI MULIA KENDARI - Achirul Slamet Sugiarto; La Ode Saidi; Natalis Ransi; Andi Tenriawaru; Ferdinand Murni Hamundu; La Surimi (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2026)
The Hati Mulia Kendari Hospital experiences difficulties in analyzing appropriate decision making. The process of determining the best employees still uses the method of adding up each criterion so that the data tends to be unstructured and inaccurate. This research aims to produce a decision support system for determining the best employees using a simple additive weighting method. Simple additive weighting is very important because it can increase efficiency, minimize errors, optimize resources, support evidence-based decisions, overcome complexity, increase decision certainty, increase competitiveness, facilitate innovation, and encourage transparency. This decision support system uses the waterfall development method to build the system, testing the system and data using the black box testing and confusion matrix method. The results of system testing using black box testing obtained results that were in accordance with user needs and the results of data testing with 36 test data using a confusion matrix with 3 outputs produced an accuracy of 94%, precision of 80% and recall of 100%. These results show that this decision support system can be implemented.